Manifold relaxation processes in a mononuclear Co(II) single-molecule magnet. (14th December 2015) - Packová, Alena; Miklovič, Jozef; Boča, Roman
Graphical abstract: Mononuclear complex [Co(Me6 tren)Cl]ClO4 shows the slow magnetic relaxation in an applied external field B DC = 0, 0.2, 0.4, and 0.8. The effective barrier to spin reversal stays approximately U / k B ∼ 20 K. The extrapolated relaxation time for the faster relaxation process varies between 3 × 10 −9 and 6 × 10 −8 s. Abstract: Mononuclear Co(II) complex [Co(Me6 tren)Cl]ClO4 has been investigated in terms of the AC susceptibility studies at various frequencies, temperatures, and external magnetic fields. In addition to the slow magnetic relaxation present even in an absence of the external field, the application of the B DC = 0.2, 0.4, and 0.8 T induces a second, slower relaxation path. The effective barrier to spin reversal is little sensitive to the magnetic field and stays approximately U / k B ∼ 20 K. The extrapolated relaxation time for the faster process varies between 3 × 10 −9 and 6 × 10 −8 s. At T = 2.0 K the detected relaxation time is (1–3) × 10 −4 s for the faster branch and 0.06–0.3 s for the slower branch, respectively.